Pengaruh Kualitas Produk dan Promosi terhadap Citra Merek Kopi Good Day di Kota Jambi - Mappadeceng, Riko; Tarmizi, Ahmad; Dewita, Lien Nancy (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The objectives of this research are as follows: 1) To determine and describe the product quality, promotion and brand image of Good Day Coffee in Jambi City. 2.) To determine the influence of product quality and promotion on the brand image of Good Day Coffee in Jambi City. The type of data required and collected in this research is quantitative data. The object of this research is Good Day Coffee customers in Jambi City. The data source in this research is Good Day Coffee customers in Jambi City who were taken through interviews by distributing questionnaires, the data and information obtained were analyzed descriptively, to analyze customer responses regarding brand image to purchasing decisions using a 5-choice scale. One brand of packaged instant coffee that is being intensively promoted using television media is the "Good Day" product. This Good Day product is produced by PT. Santos Jaya Abadi. Promotions carried out by PT. Santos Jaya Abadi to introduce new products and maintain its existence in the processed coffee industry. Based on the results of the classical assumption test analysis, it can be concluded that the normality test meets the assumptions indicated by the Kolmogorov-Smirnov test of 0.011 > 0.05. The multicollinearity test did not show a significant effect with a VIF value of 1.070 < 10 and a tolerance value of 0.935 > 0.10. In the heteroscedasticity test, the points on the plot form a pattern, so this shows that each variable contains heteroscedasticity. Based on the results of multiple linear regression analysis, it was concluded that the regression equation Y = 2.638 + 0.150X1 + 0.329X2. The value of the Coefficient of Determination (R2) is 0,213 which means that variations in changes in Y are influenced by changes in X by 21.3%. So the magnitude of the influence of product quality (X1) and promotion (X2) on the brand image (Y) of Good Day Coffee in Jambi City is 21.3% while the remaining 78.7% is influenced by other factors outside this research such as purchasing decisions, price, personal factors and so on. There is a significant positive influence between product quality and promotion together (simultaneously) on the Brand Image of Good Day Coffee in Jambi City. Partially there is an influence of product quality on brand image. This is indicated by the tcount value of 4.285 > ttable 1.662. Partially there is an influence of promotion on brand image. This is indicated by the tcount value of 3,333 < ttable 1.662.